Panel Data Analysis Study: The Impact of Indonesian Sharia Bank Financing on MSME Output Value 2021-2023 - Nur Fitriya Ningsih; Muhammad Yazid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the effect of Bank Syariah Indonesia financing on the output value of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia during the 2021-2023 period. Using a panel data approach, this study evaluates the effectiveness of Islamic financing in two main categories: working capital and investment. Data were obtained from the Central Statistics Agency (BPS) and the annual reports of Bank Syariah Indonesia. The results show that working capital financing has a significant positive effect on MSME output value, while investment financing shows a lower effect. Control variables such as Third Party Funds (DPK) and labor also have significant contributions. With a coefficient of determination of 93.04%, this study emphasizes the importance of a more inclusive Islamic financing policy focused on working capital to support MSME productivity. These results provide implications for Islamic banking and policymakers to enhance MSME development through a strategic financing approach.